2013
DOI: 10.5575/geosoc.2012.0074
|View full text |Cite
|
Sign up to set email alerts
|

The depositional environment of the singular Middle Miocene strata from southwestern Tomioka City, Gunma Prefecture, central Japan, from the view point of fossil ostracod assemblage

Abstract: We present a micropaleontological re-examination of the depositional environment of the Kojyakui-sho sediments of the Middle Miocene Obata Formation, part of the Tomioka Group, located along the Kabura-gawa River near Tajima, Tomioka City, western Gunma Prefecture, central Japan. These sediments contain sublittoral and bathyal ostracods, and were deposited in the bathyal zone on a quartz-porphyry bedrock seafloor during the late Early to early Middle Miocene. Planktonic foraminifera and ostracods within these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…1998, 2004; Tanaka et al . 2002, 2013; Irizuki, 2003; Tanaka, 2003; Tanaka, Tsukawaki & Ooji, 2004; Tanaka & Nomura, 2009; Matsuura, Irizuki & Hayashi, 2013; Tanaka, Nomura & Hasegawa, 2012). However, only seven studies have reported a Palaeogene ostracod assemblage in Japan (Yamaguchi, 2004, 2006; Yamaguchi, Matsubara & Kamiya, 2005; Yamaguchi, Nagao & Kamiya, 2006; Yamaguchi & Kamiya, 2007, 2009; Yamaguchi & Kurita, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…1998, 2004; Tanaka et al . 2002, 2013; Irizuki, 2003; Tanaka, 2003; Tanaka, Tsukawaki & Ooji, 2004; Tanaka & Nomura, 2009; Matsuura, Irizuki & Hayashi, 2013; Tanaka, Nomura & Hasegawa, 2012). However, only seven studies have reported a Palaeogene ostracod assemblage in Japan (Yamaguchi, 2004, 2006; Yamaguchi, Matsubara & Kamiya, 2005; Yamaguchi, Nagao & Kamiya, 2006; Yamaguchi & Kamiya, 2007, 2009; Yamaguchi & Kurita, 2008).…”
Section: Introductionmentioning
confidence: 99%